Does the extension of primary care practice opening hours reduce the use of emergency services? - Matteo Lippi Bruni; Irene Mammi; Cristina Ugolini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2014)
Over-crowding in Emergency Departments (EDs) generates potential inefficiencies. Using regional administrative data, we investigate the impact of an increase in the accessibility of primary care on ED visits in Italy. We test whether extending practice opening hours up to 12 hours/day reduces inappropriate ED visits. We estimate count data models, considering different measures for ED visits recorded at the list level. Since the extension programme is voluntary, we also account for the potential endogeneity of participation, using a two-stage residual inclusion and a GMM approach. Our results show that improving primary care accessibility favours a more appropriate use of EDs.
Keywords: I11; I18; C31; 330